Whistleblowing in family firms: power and justice dynamics - Lafleur, Clarisse (Journal of business ethics, 2025)
We explore how power and justice dynamics influence whistleblowing behaviour in family firms, focusing on the under-explored construct of connection power. Power and justice are two important, interrelated forces strongly affecting moral behaviour. We hypothesise a moderated moderation model and use a 2 × 2x2 between-subject experiment with 331 participants to test our conceptual model. We find that the family relation (i.e., connection power) of the wrongdoer changes what we know about the relationship between the legitimate power of the observer and whistleblowing likelihood, and that, in some instances, observers with high legitimate power are even less likely to blow the whistle than those with low legitimate power. Our exploration further reveals that, although the family relation of the wrongdoer discourages would-be whistleblowers, even those with legitimate power, organisational justice consistently increases the likelihood of whistleblowing in every case.